The Effect of Trust, Promotion, and Service Quality on the Decision to Use the Ollin Application - Rafika, Sella; Hasibuan, Anggy Qurnia Raafi; Gusteti, Yessi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2024)
This research was conducted at the Bank Nagari Koto Agung Branch Office, Block B, Sitiung 1, Sitiung District, Dharmasraya Regency. The purpose of this research was to determine the effect of Trust, Promotion, and Service Quality on the Decision to Use the Online Application at the Bank Nagari Koto Agung Branch Office. A quantitative research method was used, with data collected through a questionnaire distributed from February to March, resulting in a sample of 173 respondents selected using Accidental Sampling. The data analysis techniques applied in this study included validity tests, reliability tests, descriptive analysis, correlation analysis, multiple linear regression analysis, classical assumption tests, t-tests, F-tests, and determination tests (R²). The results of this study indicate that Trust, Promotion, and Service Quality variables have a positive and significant effect, both partially and simultaneously, on the Decision to Use the Online Application at the Bank Nagari Koto Agung Branch Office. The R² value is 0.739, which implies that 73.9% of the variation in the dependent variable can be explained by the independent variables, while the remaining 26.1% is influenced by other factors not examined in this study.